1995
DOI: 10.1002/jcp.1041650208
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of protein and DNA synthesis in mouse C2C12 satellite cells: Evidence for phospholipase d‐dependent and ‐independent pathways

Abstract: In C2C12 myoblasts, 12-O-tetradecanoylphorbol-13-acetate (TPA) stimulated a phospholipase D (PLD) to degrade phosphatidylcholine (PC) as measured by the release of choline and an increase in the formation of phosphatidic acid (PA) (or phosphatidylbutanol [PtdBuOH] in the presence of 0.5% butanol). Exogenous PLD also stimulated choline release, PA and PtdBuOH formation. The protein kinase C (PKC) inhibitor, Ro-31-8220, and PKC downregulation significantly inhibited the effects of TPA but Ro-31-8220 had no effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…There were two main reasons for this. We have observed that both the phospholipase D (Morrison et al, 1995) and insulin (Palmer et al, manuscript in preparation) signal transduction pathways controlling protein synthesis become inoperative upon fusion of C2CI2 cells. Thus, such pathways might also be uncoupled from protein degradation in these cells.…”
Section: Discussionmentioning
confidence: 92%
“…There were two main reasons for this. We have observed that both the phospholipase D (Morrison et al, 1995) and insulin (Palmer et al, manuscript in preparation) signal transduction pathways controlling protein synthesis become inoperative upon fusion of C2CI2 cells. Thus, such pathways might also be uncoupled from protein degradation in these cells.…”
Section: Discussionmentioning
confidence: 92%
“…This was performed essentially as in previous studies (25,40). Briefly, before each experiment, cells were transferred to 3 ml of serum-free DMEM containing [methyl-3 H]choline (1.33 Ci/ml) for 24 h. At the end of this labeling period, the cells were washed and incubated in DMEM for 30 min.…”
Section: Pld Activitymentioning
confidence: 99%
“…Alterations in muscle DNA, RNA and protein content may involve changes in a number of signalling pathways. Evidence from muscle cell cultures suggests that protein kinase C (PKC) plays a role in the cascade of events by which changes in activity of phospholipases affect accretion of RNA and protein (Morrison et al 1995;Thompson et al 1997) and that one or more of a group of three PKC isofoms (a, 6 and/or E ) may mediate changes in ribosomal activity and protein synthesis in muscle cells in vitro (Thompson et al 1997). This may involve changes in the activity of PKC or in the intracellular redistribution of the enzyme, i.e.…”
Section: Pregnancy: Protein Kinase C: Sheepmentioning
confidence: 99%